An identity-based broadcast signcryption scheme and its application to medical images sharing - Dang, Thu Hien (ĐHCN, 2017)
Chapter 1: Introduction. Chapter 2: Preliminaries. Chapter 3: Identity-Based Broadcast Signcryption Scheme. Chapter 4: Experimentation and Application. Chapter 5: Conclusions and Future Work.